1998
DOI: 10.1037/0735-7028.29.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Psychological practice and managed care: Results of the CAPP practitioner survey.

Abstract: Practicing members of the American Psychological Association ( APA) were surveyed regarding their work settings, activities, and greatest professional concerns in the managed care era. Results from 15,918 licensed psychologists indicated that half were full-time independent practitioners engaged principally in psychotherapy and assessment and another third were in part-time private practice.Four out of five reported a negative impact of managed care on their practices. Concerns about changes to practice and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
107
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 10 publications
4
107
0
Order By: Relevance
“…This number was 45.0% of the original 1,800 surveys mailed. Surveys using similar samples obtained comparable response rates (Phelps, Eisman, & Kohout (1998) had a 34% return after one mailing, Hatfield & Ogles (2004) obtained a 46% response rate after two mailings). Each of the vignette conditions had at least 80 surveys returned and response rates did not differ across vignettes.…”
Section: Participantssupporting
confidence: 58%
“…This number was 45.0% of the original 1,800 surveys mailed. Surveys using similar samples obtained comparable response rates (Phelps, Eisman, & Kohout (1998) had a 34% return after one mailing, Hatfield & Ogles (2004) obtained a 46% response rate after two mailings). Each of the vignette conditions had at least 80 surveys returned and response rates did not differ across vignettes.…”
Section: Participantssupporting
confidence: 58%
“…Only in this way will clinical psychologists compete successfully for the shrinking mentalhealth-care dollar. Indeed, unless psychologists can manage better their professional image and find the niche in which they are clearly considered by the public to be the practitioners of choice, independent practitioners should heed the wise counsel of the American Psychological Association and diversify their activities (Kohut, 1995;Phelps et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although the American Psychological Association has been urging clinicians to diversify their professional earning activities into areas such as consultation and research, recent surveys of practicing psychologists (Kohut, 1995;Phelps, Eisman, & Kohut, 1998) found that most clinical psychologists are maintaining the traditional model of independent practice. To maintain the traditional model, psychologists face a major challenge in the public-relations arena.…”
mentioning
confidence: 98%
“…Answering questions about the pattern and timing of change will also be of interest to the scientist-practitioner concerned with maximizing outcome and understanding the psychotherapeutic process. The answers to these questions will aid the scientist-practitioner in discerning when change should be generally expected and allowing the clinician to identify cases in which he or she should modify therapy to enhance outcome.Despite the aforementioned benefits of explicitly assessing therapeutic change, less than one third of licensed clinicians report measuring outcome in their clinical practices (Phelps, Eisman, & Kohout, 1998). To better understand clinicians' attitudes toward empirical assessment, Garland, Kruse, and Aarons (2003) conducted interviews and focus groups with a diverse sample of mental health providers who were required by the state of California to conduct outcome assessments.…”
mentioning
confidence: 99%
“…Despite the aforementioned benefits of explicitly assessing therapeutic change, less than one third of licensed clinicians report measuring outcome in their clinical practices (Phelps, Eisman, & Kohout, 1998). To better understand clinicians' attitudes toward empirical assessment, Garland, Kruse, and Aarons (2003) conducted interviews and focus groups with a diverse sample of mental health providers who were required by the state of California to conduct outcome assessments.…”
mentioning
confidence: 99%